Перспективи розширення паливної бази при використані водовугільного палива в енергетичному секторі України - Perov M.O.; Makarov V.M.; Novytskyi I.Yu.; Zhukov A.P. (General Energy Institute of the National Academy of Sciences of Ukraine, 2012)
The present situation, which was formed in Ukraine’s energy sector, requires one to use the cheapest forms of fuel, including those obtained from wastes of the technological processes of coal-enriching factories, mines, and objects of the open mining of brown coal. Such a fuel is, in particular, water-carbon fuel (WCF). Only the thermal sector of the Ministry of energy and mines of Ukraine consumes almost 90% of qualitative enriched coal, whose cost will rise in the future. Moreover, a reduction of the gas consumption in the fuel balance of electric power plants is considered as a priority task of the economic development for the nearest and middle-time prospect.A purpose of the article is to propose the methods of combustion of coal, which is transformed into water-carbon fuel, in the low-power industry and at heat power plants. The available world technologies prove the workability of and the expediency for this form of fuel to be used under certain conditions, as well as its competitiveness, in particular with regard for the varying price factors and the ecological limitations in the comparison with the layered and coal-dust combustion.The use of this new fuel is most expedient with the substitution of petroleum residue (and gas) at boiler houses. Till now, more than ten types of steam and hot-water boilers with the combustion of WCF are tested. Such boilers include the following types: DKVR, DE, BKZ-50-40 GM, BKZ-75-75-40 GM, BKZ-35-40 GM, etc.